2013
DOI: 10.1111/febs.12126
|View full text |Cite
|
Sign up to set email alerts
|

Glypican‐3: a marker and a therapeutic target in hepatocellular carcinoma

Abstract: Glypican-3 (GPC3) is a member of the glypican family. Glypicans are proteoglycans that are attached to the cell surface by a glycosyl-phosphatidylinositol anchor. They regulate the signaling activity of several growth factors, including Wnts. This regulation is based on the ability of glypicans to stimulate or inhibit the interaction of these growth factors with their respective signaling receptors. It has been clearly established that whereas GPC3 is expressed by most hepatocellular carcinomas (HCCs), this gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 59 publications
4
146
1
3
Order By: Relevance
“…In particular, the genes coding for the SPINK1 and GPC3 were recently reported to be (25)(26)(27). As described earlier by our group (28) SPINK1, also known as tumor-associated trypsin inhibitor, was typically overexpressed in HCV-positive HCCs, underlining the theory that SPINK1 may be able to interrupt apoptosis of viralinfected hepatocytes by cellular host defense (29) as one of the postulated mechanisms of this gene in hepatocarcinogegesis.…”
Section: Discussionmentioning
confidence: 54%
“…In particular, the genes coding for the SPINK1 and GPC3 were recently reported to be (25)(26)(27). As described earlier by our group (28) SPINK1, also known as tumor-associated trypsin inhibitor, was typically overexpressed in HCV-positive HCCs, underlining the theory that SPINK1 may be able to interrupt apoptosis of viralinfected hepatocytes by cellular host defense (29) as one of the postulated mechanisms of this gene in hepatocarcinogegesis.…”
Section: Discussionmentioning
confidence: 54%
“…Codrituzumab (GC33) is a recombinant, humanized monoclonal antibody that binds to human GPC3 with high affinity. The mechanism of the GC33-induced tumor growth inhibition is an antibody-dependent cellular cytotoxicity [33] . A phase I study have already shown its tolerability at doses of 20 mg/kg/week, with little response [34,35] .…”
Section: Glypican-3mentioning
confidence: 99%
“…In the same study, GPC3 expression was negative in sarcomatoid HCC, carcinoid tumors, and cholangiocarcinomas [43]. The reported sensitivity of GPC3 for HCC in the literature ranges from 75% to 100%, and in large-scale trials it ranges from 75% to 85% [26,43,47,[55][56][57].…”
Section: Discussionmentioning
confidence: 95%